Preparation of Mesoporous-Activated Carbon from Branches of Pomegranate Trees: Optimization on Removal of Methylene Blue Using Response Surface Methodology - Jassem M. Salman (Journal of Chemistry)
Mesoporous activated carbon prepared from branches of pomegranate trees (BP) using physiochemical activation (potassium hydroxide treatment and carbon dioxide gasification). Based on the central composite design (CCD), two factor interaction (2FI) and quadratic models were respectively employed to correlate the activated carbon preparation variables. The effects of the activation temperature, activation time, and chemical impregnation ratios on the carbon yield, methylene blue (MB) removal were investigated. From the analysis of variance (ANOVA), the most influential factor on each experimental design response was identified. The optimum conditions for preparing activated carbon from branches of pomegranate trees (BP) were found to be activation temperature of 620.5°C, activation time of 1.4 h, and chemical impregnation ratio of 1.5. The carbon yield was found to be 16% while the removal of methylene blue was found to be 92.5%.